Analisis Perbandingan Kinerja pada Bank Nasional, Bank Campuran, dan Bank Asing yang terdaftar di Bursa Efek Indonesia - Angel, Christania Graciella (Universitas Sam Ratulangi, 2014)
Bank performance appraisal is based on bank financial report itself. The financial report can be form balance report which give information about the financial position to the outside of bank that can be used of eksternal to assess the level of risk exist in a bank. Based on ownership consist of national bank, mixture bank and foreign bank. These banks has tight compete to show a good performance to the public. This research aimed to analyze the financial performance difference of national bank and foreign bank at the period of 2004 to 2013 with the proxy finance ratio (CAMEL ratio) consist of: Capital, Asset Quality, Management, Earnings, and Liquidity. The population in this research consist of national bank, mixture bank, and foreign bank listed on the Indonesia Stock Exchange at the period of 2004 to 2013 which amount 42 banks. Based on purposive sampling techniques, the number of samples that meet the criteria are as many as 15 banks (5 national banks, 5 mixture banks, and 5 foreign banks). Analysis technique that use in this research is t-test. As the result the usage of proxy CAMEL ratio to analyze comparison bank performance give evidence that mixture bank performance is better than foreign bank and national bank performance.